Fornsvenska textbankens material: Dalin's Then Swänska Argus 1732-1734 - Språkbanken Text (University of Gothenburg, 2024)
This corpus is the digitization by Fornsvenska textbankens of Thän Swänska Argus (1732–1734) by Olof Dalin. The resource has been automatically annotated with morphological and syntactic information.

There is also a manual transcription of this corpus available here.

Korpusen är Fornsvenska textbankens digitalisering av Olof Dalins Thän Swänska Argus (1732–1734). Resursen är automatiskt annoterad med morfologisk och syntaktisk information.

Det finns även en manuell transkription av denna korpus tillgänglig här.
Fornsvenska textbankens material: Dalins Then Swänska Argus 1732-1734
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik